2018
DOI: 10.1002/14651858.cd012812.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Home parenteral nutrition for people with inoperable malignant bowel obstruction

Abstract: We are very uncertain whether HPN improves survival or quality of life in people with MBO as the certainty of evidence was very low for both outcomes. As the evidence base is limited and at high risk of bias, further higher-quality prospective studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 71 publications
1
48
0
4
Order By: Relevance
“…A formal Cochrane review of the use of home PN in individuals with inoperable MBO found that the benefits of PN are uncertain. Among 13 observational studies, mean survival ranged from 3 to 1278 days, and adverse effects of therapy occurred in 12% of patients 53 …”
Section: Principles Of Nutrition Support In Mbomentioning
confidence: 99%
“…A formal Cochrane review of the use of home PN in individuals with inoperable MBO found that the benefits of PN are uncertain. Among 13 observational studies, mean survival ranged from 3 to 1278 days, and adverse effects of therapy occurred in 12% of patients 53 …”
Section: Principles Of Nutrition Support In Mbomentioning
confidence: 99%
“…In a systematic review evaluating 437 patients, median overall survival was only 15 to 155 days. 80,81 If adjunctive nutrition is being considered for a patient with MBO, then it is important to stratify patients based on baseline performance status. In a study of 81 patients with MBO receiving parenteral nutrition, patients with a higher performance status (i.e., Karnofsky Performance Status [KPS] Score > 50) were found to have a median survival of 183 days compared with patients with a lower performance status (KPS 50) who were found to have a median survival of 91 days (p ¼ 0.01).…”
Section: Role Of Nutritional Supportmentioning
confidence: 99%
“…While oral water‐soluble contrast may have benefit in the benign setting, there is no evidence that it is of benefit with an MBO . Total parenteral nutrition is controversial and there is no evidence for improved survival or quality of life . Palliative pharmacologic therapies have the goals of reducing intestinal inflammation and edema, and controlling pain, nausea, vomiting, and dehydration.…”
Section: Clinical Optionsmentioning
confidence: 99%